2014
DOI: 10.1186/1476-0711-13-14
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility pattern of bacterial isolates from wound infection and their sensitivity to alternative topical agents at Jimma University Specialized Hospital, South-West Ethiopia

Abstract: BackgroundWound infection is one of the health problems that are caused and aggravated by the invasion of pathogenic organisms. Information on local pathogens and sensitivity to antimicrobial agents, and topical agents like acetic acid is crucial for successful treatment of wounds.ObjectivesTo determine antimicrobial susceptibility pattern of bacterial isolates from wound infection and their sensitivity to alternative topical agents at Jimma University Specialized Hospital.MethodsA cross sectional study was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

50
119
8
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(194 citation statements)
references
References 17 publications
(32 reference statements)
50
119
8
2
Order By: Relevance
“…5 On bacteriological analysis of superficial pus culture it was found that Staphylococcus aureus 21 (42%) was the predominant species isolated followed by pseudomonas in 14 (28%) of patients. This finding is in agreement with the works of Mohammed et al, Raza MS et al and Mama et al [6][7][8] Staphylococcus was the most common isolate in superficial pus culture. The high prevalence of S. aureus infection may be because it is an endogenous source of infection.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…5 On bacteriological analysis of superficial pus culture it was found that Staphylococcus aureus 21 (42%) was the predominant species isolated followed by pseudomonas in 14 (28%) of patients. This finding is in agreement with the works of Mohammed et al, Raza MS et al and Mama et al [6][7][8] Staphylococcus was the most common isolate in superficial pus culture. The high prevalence of S. aureus infection may be because it is an endogenous source of infection.…”
Section: Discussionsupporting
confidence: 83%
“…It was also sensitive to clindamycin (82.6%), levofloxacin (69.5%) and gentamycin (60.8%). This finding is in agreement with the work of Mama et al and Raza et al 7,8 Remarkable susceptibility of gram positive bacteria to vancomycin may be due to lesser use of these antibiotics as a result of their less availability and cost.…”
Section: Antibiotic Sensitivitysupporting
confidence: 83%
See 1 more Smart Citation
“…16 A number of reports done previously on wound infection from different parts of the world indicated that S. aureus was the most frequent isolates. [17][18][19][20][21] Madsen et al, 22 Thu et al, 23 Maksimovic et al, 24 and Markovic et al, 25 reported that S. aureus were the most common pathogens associated with cases of surgical site infection in orthopedic surgery units. The study by Etok, et al, 26 66.7% gram negative and 33.3% gram positive were isolated.…”
Section: Discussionmentioning
confidence: 99%
“…Mama et al 6 in 2014 found S. aureus was the predominant organism isolated 32.4%, followed by Escherichia coli (E. coli)20%, Proteus spps 16%, coagulase negative Staphylococci 14.5%, Klebsiella pneumonia (K. pneumoniae) 10% and P. aeruginosa 8%.…”
Section: Organism Detectedmentioning
confidence: 99%